Chapter Sistemi parentali e consortili nel mondo signorile - Fiore, Alessio (Reti Medievali E-Book, 2023)
Between the 14th and 15th century, the kinship and consortium systems existing within the Italian aristocratic world significantly affected the way the territorial lordship in the hands of the lay lords were structured and managed by their owners, the self-representation of lordly prerogatives, but also the political action focused on lordships, both within and outside state frameworks. This is a key but little investigated theme. If at the beginning of the period the practices connected with kinship seem to be characterised by a strong dissimilarity, we can observe process of (relative) convergence, even if significant differences remain, particularly (but not only) between the north and south of the Peninsula. A key element in understanding these differences is the different strength of central power and its structures.